Perceived Influence of Digital Technology on Undergraduate Students’ Academics in University of Maiduguri, Borno State, Nigeria - Maduagwu, Beatrice C.; Kaku, Zakka (Kashere Journal of Education, 2022)
This study was conducted to determine the influence of digital technology on undergraduate students’ academics. It was guided by two objectives and one null hypothesis. Descriptive survey research design was adopted for the study. A sample of 378 undergraduate students was used for the study using a multistage sampling technique. Perceived Influence of Digital Technology on Undergraduate Students’ Academics Questionnaire (PIDTUSAQ) was used as an instrument for data collection. Cronbach Alpha analysis was used to estimate the internal consistency of the instrument and reliability coefficient value of 0.79. Research question was answered with descriptive statistics of mean and standard deviation. The null hypothesis was tested using independent t-test at 0.05 level of significance. Data analysis was done using the Statistical Package for Social Sciences (SPSS) version 23. Findings revealed negative influence of digital technology on undergraduate students’ academics as most of the students struggle with balancing the use of their smart phones/computers for pleasure and proper academic engagement. It was also discovered that gender had influence on the impact of digital technology on undergraduate students’ academics with females being the most influenced. Based on this, it was recommended that time management should be emphasized among undergraduate students to prevent distractions orchestrated by the inappropriate use of digital technology. Time hiatus for essential activity should be recognized and organized by students.